(untitled) (REMUNOM, 2025)
This study analyzes the impacts of adopting a Software as a Service (SaaS) system in the Municipal Health Department of Estiva/MG, focusing on improving efficiency and service quality for citizens. The digital tool was developed to optimize the management of medical requests, allowing for the scanning of documents, the organization of a patient database, and the categorization of requested procedures such as consultations, exams, follow-ups, and surgeries. The methodology was based on qualitative research, including document analysis and direct observation of administrative routines. The results show improvements in internal organization, reduction of operational errors, and better control of backlogged demand. It is concluded that the adoption of digital solutions in local public management can significantly enhance service delivery when supported by planning, training, and institutional commitment.